Zur Dynamik der Sexualproportion bei der Feldmaus, Microtus arvalis (Pallas) ... - Reichenstein, H (Die Gesellschaft, 1956)
(Uploaded by Plazi from the Biodiversity Heritage Library) No abstract provided. ...